2015
DOI: 10.1093/schbul/sbv128
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Episode Modulates Diagnosis-Related Structural Brain Abnormalities in Psychosis

Abstract: Brain volume and thickness abnormalities have been reported in first-episode psychosis (FEP). However, it is unclear if and how they are modulated by brain developmental stage (and, therefore, by age at FEP as a proxy). This is a multicenter cross-sectional case-control brain magnetic resonance imaging (MRI) study. Patients with FEP (n = 196), 65.3% males, with a wide age at FEP span (12-35 y), and healthy controls (HC) (n = 157), matched for age, sex, and handedness, were scanned at 6 sites. Gray matter volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 54 publications
(57 reference statements)
5
28
0
Order By: Relevance
“…Specifically, greater cortical thinning in the left inferior frontal gyrus, left cuneus, right middle temporal gyrus and right superior temporal sulcus was observed in NA-FEP compared to A-FEP (Qiu et al, 2013). Moreover, Pina-Camacho et al (2016) found that earlier age at NA-FEP patients had significantly smaller frontal volumes and thinner frontal, temporal, parietal, medial orbitofrontal, insular cortices as well as smaller middle frontal gyrus volumes and thinner precuneus than A-FEP .…”
Section: Accepted Manuscriptmentioning
confidence: 84%
See 1 more Smart Citation
“…Specifically, greater cortical thinning in the left inferior frontal gyrus, left cuneus, right middle temporal gyrus and right superior temporal sulcus was observed in NA-FEP compared to A-FEP (Qiu et al, 2013). Moreover, Pina-Camacho et al (2016) found that earlier age at NA-FEP patients had significantly smaller frontal volumes and thinner frontal, temporal, parietal, medial orbitofrontal, insular cortices as well as smaller middle frontal gyrus volumes and thinner precuneus than A-FEP .…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…With regard to cortical regions, four MRI studies investigated the presence of cortical thickness differences between A-FEP and NA-FEP (Pina-Camacho et al, 2016;Qiu et al, 2013;Ansell et al, 2015;(Nakamura et al, 2007). However, only two MRI studies reported significant results (Pina-Camacho et al, 2016;Qiu et al, 2013). Specifically, greater cortical thinning in the left inferior frontal gyrus, left cuneus, right middle temporal gyrus and right superior temporal sulcus was observed in NA-FEP compared to A-FEP (Qiu et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…BD > SZ in presubiculum and subiculumMathew et al 35 2014337/219/142/188PChronicMedicatedMedial temporal lobeFree Surfer3BD = HC > SZ and SAD in medial temporal cortex volume, SZ < BD < HC in hippocampal subfieldsKnochel et al 38 201421/21/0/21ChronicMedicatedHippocampusVBM3Hippocampal volume HC > BD > SZFindikili et al 122 201530/17/0/17ChronicMedicatedPineal glandROI (manual tracing)1.5Mean pineal gland volume SZ < BD < HCNenandic et al 41 201534/34/0/17PChronicMedicatedWhole brainVBM3HC > SZ prefrontal cortex and insula, temporal cortex, thalamus, and cerebellum. SZ < BD in hippocampus, DLPFC, and cerebellumKittel-Schneider et al 45 201518/23/0/30P/NPFEMedicatedAmygdalaROI (manual tracing)1.5HC > BD > SZ in amygdala volumeLaidi et al 123 201552/32/0/115P/NPChronicMedicatedCerebellumFree Surfer3SZ < HC = BD in cerebellar volumeSong et al 34 201535/71/0/44PChronicOff medicationWhole brainVBM3HC > SZ precentral gyrus, caudate, and cerebellum; HC > BD middle frontal gyrus, fusiform gyrus; BD > SZ cerebellum, temporal lobe, basal gangliaPina-Camacho et al 53 2015157/92/0/32/72PFEMedicatedWhole brainVBM, Free Surfer1.5/3HC > SZ in frontal and temporal lobe, SZ > HC in basal ganglia. HC > BD ACC, BD > HC in caudate and temporal lobe thicker temporal cortexShepherd et al 124 201534/28/12/30ChronicMedicatedWhole brainVBM3HC > SZ in hippocampus and frontal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, possible biological markers for a poor prognosis have been found in early‐onset schizophrenia. Patients who had their first episode before age 15–20 showed a significantly decreased volume and thickness of the frontal lobe, a decreased volume of the temporal lobe, and an enlarged volume of the ventricular system and the basal ganglia . Pauly et al.…”
Section: Discussionmentioning
confidence: 99%